A note on the comparative performance of the Zheng and Elisson-Elisson tests form omitted variables in regression models - Dacuycuy, Lawrence B. (Animo Repository, 2005)
In this study, we compare the performance of the Zheng (1996) and Elisson-Elisson (2000) tests for omitted variable problems in parametric regression models. The study finds that the Elisson and Elisson test has better finite sample performance relative to the Zheng test. The results also confirm the suitability of the Elisson and Elisson test for testing models in multi dimensional settings.